Demographic and Clinical Characteristics of Patients with Corneal Ectasia at Multiple Medical Centers in Saudi Arabia: A Hospital-based Study - Waleed Alghamdi; Sulaiman Aldakhil; Saif Hassan Alrasheed; Kareem Allinjawi; Mustafa Abdu; Raghda F. Mutwaly; Khaled Al Rashah; Hani M. Ghazal; Ghassan H. Radwan; Naveen Kumar Challa (Oman Medical Journal)
Objectives: We sought to explore the clinical characteristics of corneal ectasia and provide insights on related factors, including demography, ocular health, and the management trends in the Saudi population. Methods: We conducted a retrospective hospital-based chart review of patients with corneal ectasia in multiple medical centers in Saudi Arabia between 1 January and 31 December 2018. Eye care professionals diagnosed these patients based on their medical history, physical examination, and the use of Pentacam. The severity of the condition was assessed using the k median index from the Pentacam map following the modified Krumeich grading system. Results: We reviewed the medical records of 430 eyes of 215 patients with corneal ectasia. The majority (98.6%) of patients had bilateral corneal ectasia, with 202 (94.0%) having keratoconus and 13 (6.0%) having post-laser in situ keratomileusis ectasia. Males and age groups between 14 and 45 years were more affected. The mean age of onset was 7.1 years, ranging from 2–32 years, which was higher among patients from the western region. Regarding severity, 230 (53.5%) eyes presented in the initial stages, while 36 (8.4%) were in the severe stage with no significant difference between the regions studied. No significant differences were observed in mean central corneal thickness and power between patients from the central and western regions. Corneal rigid gas permeable contact lens was most used in treatment of 176 (40.9%) eyes followed by glasses in155 (36. 0%), while corneal cross-linking was the common surgical intervention (10.9%), followed by penetrating keratoplasty (3.0%). Conclusions: Most keratoconus patients had a bilateral mild stage of the disease and were in their third decade. This high rate of bilaterality of diseases during diagnosis may be due to misdiagnosis in the initial stages, which highlights the importance of community and eye care professionals’ awareness of comprehensive eye examinations and regular follow-up, including corneal topography assessments of both eyes.